2019
DOI: 10.3390/s19204538
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Predicting Glycaemia ‘On the Fly’ with Constrained IoT Devices in Type 1 Diabetes Mellitus Patients

Abstract: Type 1 Diabetes Mellitus (DM1) patients are used to checking their blood glucose levels several times per day through finger sticks and, by subjectively handling this information, to try to predict their future glycaemia in order to choose a proper strategy to keep their glucose levels under control, in terms of insulin dosages and other factors. However, recent Internet of Things (IoT) devices and novel biosensors have allowed the continuous collection of the value of the glucose level by means of Continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…There are methods showing good accuracy in predicting BG based on preceding CGM records, such as methods utilizing convolutional neural networks [24], [25], which shown RMSE of 1.21 (for the best patient) and 1.85 mmol/L (in average) respectively for BG prediction 60 minutes ahead, which are good values concerning prediction for type 1 diabetes patients). The comparable result was shown recently utilizing random forest in the same setting [26]. But the requirement of CGM systems to be constantly utilized in order to predict BG is expensive and inapplicable in a wide clinical practice for GDM patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There are methods showing good accuracy in predicting BG based on preceding CGM records, such as methods utilizing convolutional neural networks [24], [25], which shown RMSE of 1.21 (for the best patient) and 1.85 mmol/L (in average) respectively for BG prediction 60 minutes ahead, which are good values concerning prediction for type 1 diabetes patients). The comparable result was shown recently utilizing random forest in the same setting [26]. But the requirement of CGM systems to be constantly utilized in order to predict BG is expensive and inapplicable in a wide clinical practice for GDM patients.…”
Section: Discussionsupporting
confidence: 68%
“…All the models exhibit adequate accuracy that allows them to be used in patient assistance. The developed model in comparison to others does not require microbiome data as models by Zeevi et al [21] and Mendes-Soares et al [22] or continuous blood glucose measurements on the time of prediction as models by Li et al [24], Zhu et al [25] and Rodriguez-Rodriguez et al [26], which makes it much more accessible for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This approach fixes the over-fitting problem of decision trees. Seo et al [ 43 ], Güemes et al [ 60 ], Vahedi et al [ 33 ], G Noaro et al [ 72 ], Vu et al [ 47 ], Reddy et al [ 40 ], Chen et al [ 30 ], Dave et al [ 52 ], Calhoun et al [ 45 ], Amar et al [ 75 ], Hidalgo et al [ 77 ], and Rodriguez et al [ 79 ] have all used RF for predicting/detecting hypoglycemia. Ruan et al [ 31 ] and Cappon et al [ 66 ] used the XGboost algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…When a test point is brought to the model, SVM maps it to one of the various categories and then assigns it a label. Marling et al [ 32 ], Mosquera-Lopez et al [ 48 ], Seo et al [ 43 ], Güemes et al [ 60 ], Oviedo et al [ 68 ], Vehi et al [ 59 ], Chen et al [ 30 ], Bertachi et al [ 41 ], and Rodriguez et al [ 79 ] have all used SVM.…”
Section: Resultsmentioning
confidence: 99%
“…Gaussian Processes (GPs) with Radial Basis Function Kernels (RBF) [52] and other forms of comparative strategy create consistency overall and allow for a limitless quantity of basic functions, but these are rarely used, even though some past research has demonstrated that it can show promise [53].…”
Section: Forecastingmentioning
confidence: 99%